The Chemistry and Physics of Engineering Materials. Volume 2, - Berlin, Al. Al., 1940-; Joswik, Roman; Vatin, Nikolai I. (CRC Press LLC ; Apple Academic Press, 2015)
This new volume focuses on the limitations, properties, and models in the chemistry and physics of engineering materials that have potential for applications in several disciplines of engineering and science. Contributions range from new methods to novel applications of existing methods.The collection of topics in this volume reflects the diversity of recent advances in chemistry and physics of engineering materials with a broad perspective that will be useful for scientists as well as for graduate students and engineers. This new book presents leading-edge research from around the world.Topic.